Characteristics of infections associated with health care and use of antibiotics in a COVID-19 Intensive Care Unit, in northern Peru: 2020-2021 - Cavalcanti-Ramírez , Sofía (2023)
Objective: To describe the frequency of HAIs and the use of antibiotics in a COVID ICU in northern Peru. Material and Methods: cross-sectional descriptive study. 85 stories were reviewed. Results: median age= 57 years, IQR (49-78); 70% men; 74/85 on a ventilator, median in days= 13 (IQR=7-45). HAI frequency: 28.2%: Ventilator-associated pneumonia 79.1%; 26/85 had at least one culture: 22/26 bronchial secretions: 10/26 Acinetobacter baumani, 10/26 Pseudomonas Aeruginosa; 8/10 of Acinetobacter and 5/10 of Pseudomonas were multidrug resistant; 100% of patients received antibiotics; 63% Carbapenems (36% Imipenem and 27% Meropenem) and 22% third-class cephalosporins (14% Ceftazidime and 8% Ceftriaxone); mortality: 30.6%. Of the 19 VAP, 7/19 were due to Acinetobacter Baummani and 10/19 due to Pseudomonas Aeruginosa. Of the deceased, 19% had Acinetobacter baumani and 11% had Pseudomonas Aeruginosa. Conclusion: the most frequent germs: Acinetobacter and Pseudomona, all patients received antibiotics and the most frequent was imipenem.